Community-based rehabilitation service experience, satisfaction and behavioural intentions: the parent’s perspective / Nur Balqis Shufian, Prof. Dr. Boo Ho Voon and Dr. Johari Abdullah - Shufian, Nur Balqis; Boo, Ho Voon; Abdullah, Johari (Universiti Teknologi MARA, Kedah, 2024)
This study aims to assess the experiences of parents who sent their children to Community-Based Rehabilitation (CBR) services in Sarawak. The six dimensions in this study include trainee orientation, performance orientation, interfunctional coordination, long-term orientation, employee orientation, and competitor orientation. While the number of CBR centres may be growing, however, there are still concerns about the service effectiveness, long-term impact, and transformative effects on persons with disabilities. Issues like poverty, barriers to education and employment, and substandard living environments lead to adverse health conditions and limited access to healthcare for Persons with Disabilities (PWDs). This conceptual paper aims to identify key factors that contribute to parental satisfaction and their intentions regarding rehabilitation services. The proposed research will engage a simple random sampling method to collect data from a sample size of 322. A cross-sectional study will be employed, and the questionnaire will be distributed to the parents of the trainees. The findings of this study will be instrumental in enhancing service delivery to meet the needs of persons with disabilities (PwDs), ensuring the sustainability of the CBR sector. This research fills the gap in customer experience in rehabilitation studies regarding parental experience with CBR services.